Fundamentals and applications of magnetic materials - Krishnan, Kannan M. (Oxford Oxford University Press, 2016)
This book provides a comprehensive discussion of magnetism, magnetic materials and related applications. It covers the physics of magnetism, magnetic phenomena in materials, size and dimensionality effects and applications including information storage, spin electronics, and biomedicine.
Keywords: Magnetic materials; Magnetism